Perceptions of Students towards Culturally Responsive Pedagogy - Singh, Shireesh Pal (Voices of Teachers and Teacher Educators, 2022)
Culturally responsive teaching demands diligent efforts and dedication for the high-level success of diverse students. A culturally responsive teacher recreates teaching-learning situations so that students work collaboratively with their peers and teachers to improve their achievement. Those practicing culturally responsive pedagogy must have high and positive expectations for their students to help them achieve academic success and reach their maximum potential. This research aimed to determine students’ perception of culturally responsive pedagogy, as their responses will help to develop a framework for the same. Investigator selected 200 school students as a sample of research. A self-made three-point Likert scale was used to collect data, parametric and non-parametric statistics were used to analyze the data. The research results reveal that most students positively perceive culturally responsive pedagogy and have shown no differences when we compared them based on gender, category, and locale.